EFISIENSI PENGGUNAAN PUPUK FOSFOR PADA TANAMAN JAGUNG DENGAN APLIKASI EKSTRAK PELARUT FOSFAT - Edy Edy; Bakhtiar Ibrahim (Percetakan Umi Toaha Makassar, 2022)
Increasing corn production by minimizing the use of fertilizers, especially phosphorus (P) fertilizers can be done by maximizing the release of phosphorus nutrients bound in the soil. This study aims to make efficient use of phosphorus fertilizer by utilizing phosphate solvent extract (EPF) in increasing the growth and production of maize. The study was conducted from November 2018 to March 2019, which was arranged in a randomized block design with package treatments: EPF 100 mL/L + P 50 kg/ha (0.7 g/plant), EPF 150 mL/L water + P 100 kg /ha (1.4 g/plant), EPF 200 mL/L water + P 150 kg/ha (2.1 g/plant), EPF 150 mL/L water + P 50 kg/ha (0.7 g/ plants) and EPF 200 mL/L water + P 100 kg/ha (1.4 g/plant). Each treatment combination was repeated three times. The results showed that 1) The availability of P in the soil increased after being treated with a combination of EPF and P reaching 8.61 ppm compared to only 1.15 ppm before treatment. 2) The combination of treatment with EPF 100 mL/L water + P 0.7 g/plant has a very good effect on the level of P uptake. 3) The combination of Phosphate Solvent Extract 200 mL/L water + P 1.4 g/plant has a good effect on growth and maize production of Srikandi Putih Variety with Phosphorus Use Efficiency of 0.82%.